DNA fingerprinting analyses of M tuberculosis-complex isolates from the Free State, South Africa, as part of a multidisciplinary study - Van der Spoel-van Dijk, Anneke; Mokhethi, Zac; Khumalo, Macala; Shamputa, Choala; Matebesi, Zacheus; Van Rensburg, Dingie; Portaels, Françoise; Rigouts, Leen (University of the Free State, 2005)
The objective of this study was to serve as a complement to socio-economic analyses of TB patients in a DOTS system, providing microbiological data and documenting the TB population dynamics. Sputum samples were collected from smear-positive TB patients in the Goldfields, Thaba Nchu and Qwaqwa areas. Laboratory analyses comprised the culturing of Mycobacterium tuberculosis isolates and DNA fingerprinting. The primary aim was hampered by problems encountered during specimen sampling, inadequate resources, and a low culture-positivity rate. Nevertheless, the fingerprinting data of a random sample showed a heterogenous TB population, suggesting that reactivation might be an important factor in the area studied. Clustering was the highest in the mining area. Preliminary data from serial isolates also detected possible re-infection during treatment or initial mixed infections in five of the eleven patients.

Die doel was om die sosio-ekonomiese analise van TB-pasiënte in ’n DOTS-sisteem met mikrobiologiese data te komplementeer en om die TB-populasiedinamika te dokumenteer. Sputummonsters is versamel van smeer-positiewe TB pasiënte in die Goudveld, Thaba Nchu en Qwaqwa. Laboratoriumanalise het bestaan uit die kweking van Mycobacterium tuberculosis isolate en DNS-vingerafdrukke. Die primêre doel- stelling is gekortwiek deur probleme wat ondervind is met monsterversameling, gebrek aan fondse en ’n lae positiewe kwekingswaarde. Nogtans het vingerafdruk- data van ’n ewekansige monster ’n heterogene TB-populasie getoon wat suggereer dat heraktivering van vorige infeksies ’n belangrike faktor in die studiepopulasie mag wees. Die grootste saambundeling was teenwoordig in die myngebied. Verder toon voorlopige data van opeenvolgende isolate moontlike herinfeksie gedurende behandeling of aanvanklike gemengde infeksies in vyf van die elf pasiënte.
Keywords: Tuberculosis; South Africa; Free State; DNA fingerprinting